2015
DOI: 10.18844/gjflt.v5i0.50
|View full text |Cite
|
Sign up to set email alerts
|

The rhetorical organization of research article discussion sections: An investigation into genre evolution in applied linguistics

Abstract: The present study aimed to investigate the evolution of the rhetorical structure of research article discussions in three prestigious journals covering the two chronological periods of 1980-1989 (group A) and 2005-2010 (group B). It also studied changes in the application of the two most frequently used verb tenses − the simple present tense and the simple past tense − over the two time periods. Overall, 115 published articles were selected from the aforementioned journals. Move analysis was accomplished throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…Thus, their proposed model comprised eight moves as indicated in Table 3. Furthermore, by comparing the local and international applied linguistics journals, Jalilifar et al (2012) found the tendency of low frequency of local RA discussion's Move 5 (reference to previous research), indicating that local writers did not relate their work to previous research.…”
Section: Genre and Move Analysismentioning
confidence: 68%
See 3 more Smart Citations
“…Thus, their proposed model comprised eight moves as indicated in Table 3. Furthermore, by comparing the local and international applied linguistics journals, Jalilifar et al (2012) found the tendency of low frequency of local RA discussion's Move 5 (reference to previous research), indicating that local writers did not relate their work to previous research.…”
Section: Genre and Move Analysismentioning
confidence: 68%
“…Finally, Jalilifar et al (2012) investigated one discipline, applied linguistics, with a comparison between local (Iranian) and international journals. They applied the Dudley-Evans model and agreed with Peacock's previous assertion that it needed modification.…”
Section: Genre and Move Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The 2004 framework, more encompassing, is an improved version of the 1900 model successfully addressing most of the constraints pointed out by the scholars against the old one (Ozturk, 2007). Hence, several works have adopted this framework in analyzing research introduction across different fields (see Farnia & Barati, 2017;Isik Tas, 2008;Jalilifar, 2010;Lintao & Erfe, 2012;Minaei & Sabet, 2017;Sheldon, 2011).…”
Section: Literature Review 1theoretical Basesmentioning
confidence: 99%